Stackable manipulator for mobile manipulation robot - Lee, H.; Oh, Y.; Shon, W.H.; Choi, Y. (Proceedings - IEEE International Conference on Robotics and Automation, 2012)
This paper proposes a new manipulator concept applied to a mobile robot manipulation system for reducing robot size and weight or increasing its work capacities such as a payload, operating radius, and operating speed. In detail, we propose a new robotic manipulator that uses stackable 4-BAR mechanisms for mobile manipulation robot. The proposed mechanism provides a clear advantage in which all the actuators can be separated from the working joints. Thus, the mechanism is able to select the Center of Mass (CoM) and the Zero-Moment Point (ZMP) in arbitrary points without any support from ZMP controller or ZMP compensation method. To confirm efficiency of the new manipulator, this paper addresses a design method using the simplified beam theory, based on the well-known Finite Element Method (FEM) for structural stiffness analysis of linkages. The reason behind this is that the CoM and ZMP are dependent on the weight of the motors and the linkages. Ultimately, we show the efficiency of the proposed stackable manipulator through simulations and experiments. ？ 2012 IEEE.